O EMPREENDIMENTO SOCIAL: FATORES DE SUCESSO. O CASO DA NATURAL FASHION, COOPERATIVA EM CAMPINA GRANDE, PARAÍBA - Lima, Kenya do Couto Ferreira (2009)
This study identifies the success factors and characteristics of a social enterprise and, in particular the cooperative Natural Fashion, located in Campina Grande - PB. An exploratory research was used, based on a bibliographic and participant research, in a qualitative approach. The bibliographic research was based on authors that bring a reflection about the context of cooperatives and social enterprises. It refers to the important role of this cooperative in your region, through practices consistent with sustainability and socialenvironmental responsibility. It rests also on a case study from the cooperative Natural Fashion which emphasizes the need to explore for new entrepreneurs aiming to develop their skills and abilities. The results of this research indicate that the best business practices social and sustainable.